PSYCHOLINGUISTIC ANALYSIS OF NAPOLEON’S CHARACTER IN GEORGE ORWELL’S “ANIMAL FARM” (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This thesis analyzes the psycholinguistic features of the main character Napoleon in George Orwell’s novel Animal Farm. The study explores the linguistic and psychological mechanisms that reveal the inner world of the character and his methods of manipulating others through language. During the research, special attention is paid to dialogue between characters, linguistic expressions of psychological states, direct and indirect forms of speech, and intonation as key psycholinguistic components.